Intraoperative Transfusion of Fresh Frozen Plasma Predicts Morbidity Following Partial Liver Resection for Hepatocellular Carcinoma - Bednarsch, Jan (J Gastrointest Surg, 2020)
BACKGROUND: The reduction of perioperative morbidity is a main surgical goal in patients undergoing partial hepatectomy for hepatocellular carcinoma (HCC). Here, we investigated clinical determinants of perioperative morbidity in a European cohort of patients undergoing surgical resection for HCC. METHODS: A total 136 patients who underwent partial hepatectomy for HCC between 2011 and 2017 at our institution were included in this analysis. The associations between major surgical complications (Clavien-Dindo ≥ 3) and overall morbidity (Clavien-Dindo ≥ 1) with clinical variables were assessed using univariate and multivariable binary logistic regression analysis. RESULTS: Multivariable analysis identified the Child-Pugh-Score (CPS, HR = 3.23; p = 0.040), operative time (HR = 5.63; p = 0.003), and intraoperatively administered fresh frozen plasma (FFP, HR = 5.62; p = 0.001) as independent prognostic markers of major surgical complications, while only FFP (HR = 6.52; p = 0.001) was associated with morbidity in the multivariable analysis. The transfusion of FFP was not associated with perioperative liver functions tests. CONCLUSIONS: The intraoperative administration of FFP is an important independent predictor of perioperative morbidity in patients undergoing partial hepatectomy for HCC. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11605-020-04652-0) contains supplementary material, which is available to authorized users.